El derecho al honor, la honra y buena reputación: Antecedentes y regulación constitucional en el Ecuador - Darío Echeverría Muñoz (Ius Humani. Jornal do direito, 2020)
The purpose of this article is to analyze the right of honor, image, and good reputation that everyone has in their favor, established in Article 66, number 18 of the Ecuadorian Constitution. There will be a revision of its western historical roots and, subsequently, a comparative study from its first normative regulation to the present day based on the constitutions that have been in force and how this right evolved throughout its national legal history. Besides, a brief analysis of national jurisprudence will be considered to determine its scopes and delimitations, as well as its protection mechanism if it has been disrespected. This legal essay consists of four parts: historical background, constitutional regulation, jurisprudence, and finally its conclusions. The conclusions show how this right is related to human dignity, whose concept is the fundamental starting point for it to be recognized worldwide within modern constitutions leading to concrete mechanisms for its effective guardianship. It also reminds us that personal freedom ends where the rest of our fellow men begin.